Dental Caries Prevalence and Tooth Loss in Chilean Adult Population: First National Dental Examination Survey. (18th December 2012) - Urzua, I.; Mendoza, C.; Arteaga, O.; Rodríguez, G.; Cabello, R.; Faleiros, S.; Carvajal, P.; Muñoz, A.; Espinoza, I.; Aranda, W.; Gamonal, J.
Abstract : The purpose of this study was to assess the prevalence of dental caries, tooth loss, and risk factors among adult population of Chile. Furthermore, age, gender, and behavioural specific differences in caries prevalence and tooth loss were examined. A national stratified multistage probabilistic sample design in two-age cohorts was applied to the Chilean population. A sample of 1553 adults, comprising 1088 individuals aged 35–44 and 465 senior individuals aged 65–74, were examined. The DMFT was evaluated following WHO recommendations using diagnostic criteria of caries lesions into dentin. The data were analyzed by univariate and multivariate models using logistic regression analyses. Results showed a mean DMFT of 15.06 in the 35–44-year-old group and of 21.57 in the 65–74 group. Factors related to tooth loss in the 35–44 group through univariate logistic regression were depression (OR 1.9 CI 95% 1.26–2.85), education level <12 years (OR 2.24 CI 95% 1.31–3.73), personal income (OR 1.51 CI 95% 1.04–2.19), and familiar income (OR 2.05 CI 95% 1.34–3.13), and through multivariate logistic regression in the same age group were depression (OR 1.93 CI 95% 1.24–3.0), education level <12 years (OR 1.94 CI 95% 1.2–3.14), and familiar income (OR 1.71 CI 95% 1.09–2.68). Factors related to tooth loss in the 65–74-year-old group through univariate logistic regression were education level <12 years (OR 2.54 CI 95% 1.3–4.96) and personal income (OR 1.66 CI 95% 1.05–2.63), and for multivariate logistic regression in the same age group, it was education level <12 years (OR 2.51 CI 95% 1.21–5.18). In conclusion, adult population in Chile showed a high prevalence of dental caries and tooth loss, as age, education level, personal and familiar incomes, and depression are being the main risk factors.